2022
DOI: 10.1332/204674321x16226480242482
|View full text |Cite
|
Sign up to set email alerts
|

Positioning flexibly scheduled ECEC in the chain of childcare by parents working non-standard hours

Abstract: This study examined how Finnish parents working non-standard hours (N=18) positioned institutional flexibly scheduled early childhood education and care (ECEC) as a link in their chain of childcare. Interview data, analysed following the principles of discursive psychology, yielded three discourses on flexibly scheduled ECEC: the discourse of the child’s best interest, the discourse of the labour market, and the discourse of equality of opportunity for the child. Flexibly scheduled ECEC was positioned in these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The results show that parents do not use available services to their full potential, which may be related to the negative stigma associated with extended hours ECEC (Anme et al, 2010;De Schipper et al, 2003;De Schipper et al, 2004;Halfon & Friendly, 2015;Jordan, 2008;Moilanen, 2019;Peltoperä, 2021;Peltoperä et al, 2017;Statham & Mooney, 2003). Therefore, the cultural expectations in general society with respect to non-standard hours of both work and childcare could be more accommodating (see also Krapf, 2014;Moilanen, 2019;Peltoperä, 2021). In addition to developing ECEC services, parents' possibilities to influence their working hours could be better considered, as these vary across work domains, occupations and gender (Immonen, 2020).…”
Section: Implications For Policy and Practicementioning
confidence: 98%
See 2 more Smart Citations
“…The results show that parents do not use available services to their full potential, which may be related to the negative stigma associated with extended hours ECEC (Anme et al, 2010;De Schipper et al, 2003;De Schipper et al, 2004;Halfon & Friendly, 2015;Jordan, 2008;Moilanen, 2019;Peltoperä, 2021;Peltoperä et al, 2017;Statham & Mooney, 2003). Therefore, the cultural expectations in general society with respect to non-standard hours of both work and childcare could be more accommodating (see also Krapf, 2014;Moilanen, 2019;Peltoperä, 2021). In addition to developing ECEC services, parents' possibilities to influence their working hours could be better considered, as these vary across work domains, occupations and gender (Immonen, 2020).…”
Section: Implications For Policy and Practicementioning
confidence: 98%
“…For example, Moilanen (2019) found that despite the subjective right of children to institutional ECEC in Finland, many Finnish parents working non-standard hours continue to face childcare-related problems to the same extent as their counterparts in the UK and the Netherlands, where institutional childcare during extended hours is extremely limited. These problems may have to do with the negative stigma attached to institutional childcare during non-standard hours that has been observed in some Finnish (Moilanen, 2019;Peltoperä, 2021;Peltoperä et al, 2017) and international (Anme et al, 2010;De Schipper et al, 2003;De Schipper et al, 2004;Halfon & Friendly, 2015;Jordan, 2008;Statham & Mooney, 2003) studies as well as the strong cultural ideals favouring informal homecare (Verhoef et al, 2016).…”
Section: Cultural Frames Related To Childcare and Ececmentioning
confidence: 99%
See 1 more Smart Citation